Juvenile polyautoimmunity in a rheumatology setting (2019)
Overt polyautoimmunity (PolyA) corresponds to the presence of more than one well-defined autoimmune disease (AD) manifested clinically in a single patient. The current study aimed to describe the main characteristics of juvenile PolyA in a pediatric rheumatology setting and analyze the chronological aspects, index cases, familial autoimmunity, and clustering pattern. This was a cross-sectional and multicenter study in which 313 children with overt PolyA were included. Patients were systematically interviewed and their medical records reviewed using a questionnaire that sought information about demographic, clinical, immunological, and familial characteristics. A hierarchical cluster analysis was done to determine similarities between autoimmune diseases based on PolyA. PolyA occurred simultaneously in 138 (44%) patients. Multiple autoimmune syndrome was observed in 62 (19.8%) patients. There were 25 index diseases of which, systemic lupus erythematosus (SLE, n = 134, 42.8%), juvenile idiopathic arthritis (JIA, n = 40, 12.7%), Hashimoto's thyroiditis (HT, n = 24, 7.66%), immune thrombocytopenic purpura (ITP n = 20, 6.39%), antiphospholipid syndrome (APS, n = 15, 4.79%), and vitiligo (VIT, n = 15, 4.79%) were the most frequent and represented 79.23% of the total number of patients. Familial autoimmunity influenced PolyA. A high aggregation of autoimmunity was observed (? r = 3.5). Three main clusters were identified, of which SLE and APS were the most similar pair of diseases (based on the Jaccard index) followed by HT and JIA, which were related to ITP and Sjögren's syndrome. The third cluster was composed of localized scleroderma and VIT. Our findings may assist physicians to make an early diagnosis of this frequent condition. Pediatric patients with ADs should be systematically assessed for PolyA. © 2019